Torture Responses in Bangladesh: The Way Forward (Dhaka University Law Journal, 2025)
Bangladesh is one of the state parties of the United Nations Convention against Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment 1984 popularly known as UN Convention against Torture. In accomplishment of her international obligations under this Convention for effective prevention of torture in normative and institutional segments, she is in headway with constant responses against torture. These responses necessitate commendation on numerous explicit techniques entail to vanquish these hard edges. The aim of this article, however, is to assist the concerned authorities of the government to have a draft outline on the overall viable ways out from the numerous snags encountered in custodial torture practices prevalent in Bangladesh.Dhaka University Law Journal Vol.35, Issue.2, December 2024 P. 89-104